Low temperature cement slurry and its preparation method and application

CN118184275BActive Publication Date: 2026-10-27CHINA NAT PETROLEUM CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211605266.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2026-10-27
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

然而目前常见早强剂仍然存在一些问题:①最广泛使用的氯化钙早强剂易使水泥浆流变性能变差,出现下灰难、注替时稠度高的问题,甚至出现“假凝”现象;②钾盐早强剂中,K+由于不参与水泥水化,易在水泥石表面析出,特别是在低温下水泥石表层结晶,进而膨胀开裂,造成水泥石表面出现缺陷;③常见中-低早强剂作用温度10-30℃,对低温、超低温下水泥浆早强效果不明显,更甚者出现水泥浆中水凝结成冰,水泥石无强度发展,增加固井作业风险

Benefits of technology

[0033]本发明还提供了上述低温水泥浆在油气井固井中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003998513380000051
    Figure BDA0003998513380000051
  • Figure BDA0003998513380000052
    Figure BDA0003998513380000052
  • Figure BDA0003998513380000061
    Figure BDA0003998513380000061
Patent Text Reader

Abstract

The application provides a low-temperature cement slurry and a preparation method and application thereof. The cement slurry comprises, by weight, 100 parts of cement, 5-20 parts of a cement base material, 5-15 parts of a low-temperature active material, 1-6 parts of an early strength agent, 0-15 parts of a lightening agent, 0.5-2 parts of a dispersing agent, 0.5-2.5 parts of a fluid loss additive, 0.1-1 part of a retarder, 0.1-1 part of an antifoaming agent and 40-80 parts of water. The early strength agent comprises lithium chloride, sodium sulfate, sodium thiosulfate, sodium aluminate, triethanolamine or a combination of two or more thereof. The low-temperature cement slurry has the characteristics of early strength, micro-expansion and adjustable cement comprehensive performance, and can meet the well cementing technical requirements in low-temperature formations such as deep water and polar regions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cementing admixtures for oil and gas wells, specifically relating to a low-temperature cement slurry, its preparation method, and its application. Background Technology

[0002] Deep-sea and polar regions possess enormous potential for oil and gas resource development. As these regions increasingly become hubs for oil and gas exploration and development, cryogenic cement slurries and their key additives have become crucial for ensuring the safe and effective operation of cryogenic cementing. The low temperatures in deep-sea and polar regions, particularly in the Arctic permafrost where surface temperatures can drop below -5°C, cause conventional cement slurry systems to exhibit extremely slow hydration processes and strength development during cementing operations. In some cases, water in the cement slurry may even freeze, failing to participate in the hydration reaction and resulting in a cement slurry that lacks solidification and strength, thus failing to provide safety for subsequent drilling operations. Therefore, the addition of cryogenic reinforcing materials to the system to shorten the cement slurry setting time and increase cement stone strength at low temperatures plays a vital role in ensuring the overall performance of the cryogenic cement slurry system, guaranteeing operational safety, and improving cementing quality.

[0003] Currently, there are many types of medium- and low-temperature early-strength agents, mainly inorganic salt-based, which can improve the early strength of cement stone and shorten the setting time. However, some problems still exist with common early-strength agents: ① The most widely used calcium chloride early-strength agent easily deteriorates the rheological properties of cement slurry, leading to problems such as difficulty in cementing, high consistency during injection, and even "false setting"; ② Among potassium salt early-strength agents, K... + Because it does not participate in cement hydration, it is easy to precipitate on the surface of cement stone, especially at low temperatures, the surface of cement stone crystallizes, which then expands and cracks, causing defects on the surface of cement stone; ③ Common medium-low early strength agents have an operating temperature of 10-30℃, and their effect on early strength of cement slurry at low and ultra-low temperatures is not obvious. In some cases, water in cement slurry freezes into ice, cement stone does not develop strength, and the risk of cementing operation is increased.

[0004] To address the above technical problems, existing technologies disclose various low-temperature early-strength and toughness cement slurry technologies. For example, CN106986584 discloses a low-temperature high-strength and toughness cement slurry system, which consists of cement, low-temperature active materials, early-strength agents, expansive toughening materials, dispersants, and water loss reducing agents. The low-temperature active materials are a combination of slag powder and ultrafine cement, and the early-strength agents are a combination of calcium chloride, sodium carbonate, and calcium metasilicate. Results show that the cement slurry system disclosed in this patent can effectively improve the defects of conventional cement stone, such as slow strength development, low strength, and high brittleness at low temperatures. However, this technology uses slag powder as the low-temperature active material, failing to consider that while slag powder increases early strength, it also increases the water demand of the cement slurry, causing it to lose fluidity. Simultaneously, calcium chloride, sodium carbonate, and calcium metasilicate can all cause thickening of the cement slurry, even leading to "flash setting," which greatly increases the risk of cementing accidents.

[0005] While existing technologies, represented by the aforementioned patents, have made significant progress in low-temperature cement slurry in terms of early strength and toughness expansion at low temperatures, their anti-icing effect and early strength performance under extremely low-temperature conditions (0-5℃), especially near the freezing point (0℃), are not ideal. Furthermore, the low-temperature reinforcing materials for cement slurry in existing technologies generally have a significant impact on fluidity. Therefore, developing a low-temperature reinforcing material for cement slurry with a lower applicable temperature range is of great importance to ensure the cementing quality of polar or deep-sea low-temperature formations. Summary of the Invention

[0006] To address the aforementioned problems, the present invention aims to provide a low-temperature cement slurry, its preparation method, and its application. This cement slurry facilitates the early strength development of cement stone in low-temperature environments (0-5℃), and features early strength, micro-expansion, and adjustable comprehensive cement performance, thus meeting the cementing technology requirements of low-temperature formations such as deep water and polar regions.

[0007] To achieve the above objectives, the present invention provides a low-temperature cement slurry, which, by weight, comprises: 100 parts cement, 5-20 parts cement base material, 5-15 parts low-temperature active material, 1-6 parts early-strength agent, 0-15 parts weight-reducing agent, 0.5-2 parts dispersant, 0.5-2.5 parts water loss reducing agent, 0.1-1 part retarder, 0.1-1 part defoamer, and 40-80 parts water;

[0008] The accelerator includes one or more of lithium chloride, sodium sulfate, sodium thiosulfate, sodium aluminate, triethanolamine, and sodium metasilicate. Using these accelerators of the present invention can shorten the strength development time of cement paste and promote the strength development of cement stone.

[0009] According to a specific embodiment of the present invention, preferably, the amount of the retarder added is 0.1-0.5 parts.

[0010] According to a specific embodiment of the present invention, preferably, the amount of the weight-reducing agent added is 0.001-15 parts; more preferably, the weight-reducing agent includes glass microspheres; the purpose of adding the weight-reducing agent (e.g., glass microspheres) is to adjust the density of the cement slurry and slow down heat loss and prevent the internal temperature of the cement slurry from dropping too quickly, and the amount added is 0-15 parts. If a low-density cement slurry is required, then the weight-reducing agent glass microspheres need to be added; if a conventional density cement slurry is required, then the glass microspheres do not need to be added.

[0011] According to a specific embodiment of the present invention, preferably, the cement comprises Grade G oil well cement.

[0012] According to a specific embodiment of the present invention, preferably, the cement base material includes sulfoaluminate cement and / or magnesium phosphate cement. The cement base material of the present invention can accelerate the hydration heat release and hydration rate of cement, shorten the initial setting time of cement paste, and increase the density of cement stone, thereby achieving salt corrosion resistance, impermeability, and prevention of pore water crystallization and freeze-thaw cracking of cement stone. In addition, the cement base material has micro-expansion characteristics, which can solve problems such as expansion and cracking caused by the volume expansion of water crystallization in the pores of cement stone. It has expansion, early strength, and freeze-thaw resistance effects, and at the same time, it has good rust prevention ability for reinforcing steel and can prevent chloride and sulfate early strength agents from corroding the casing pipe.

[0013] According to a specific embodiment of the present invention, preferably, the sulfoaluminate cement is calcium sulfoaluminate cement.

[0014] According to a specific embodiment of the present invention, preferably, the low-temperature active material includes metakaolin. The low-temperature active material has high hydration activity, and when activated in conjunction with an early-strength agent, it can shorten the initial setting time of cement paste, improve the early strength of cement stone, and compensate for the cracking of cement stone caused by volume shrinkage under low-temperature conditions. Using metakaolin as the low-temperature active material allows it to react with metal ions in the early-strength agent (alkali activator) to produce a larger amount of hydration products and release heat. Simultaneously, the fine particle size of metakaolin can fill dense voids, making the cement-based material more compact.

[0015] According to a specific embodiment of the present invention, preferably, the metakaolin has a purity ≥95% and a density ≥2.50 g / cm³. 3 , mesh number ≥ 5000 mesh.

[0016] According to a specific embodiment of the present invention, preferably, the early strength agent is a combination of lithium chloride, sodium sulfate and sodium aluminate in a weight ratio of 2-4:1-2:0.2-1, more preferably 3:1.5:0.5, and more preferably, further includes triethanolamine.

[0017] According to a specific embodiment of the present invention, preferably, the early strength agent is a combination of lithium chloride, sodium thiosulfate and sodium aluminate in a weight ratio of 2-4:1-2:0.2-1, more preferably 3:1.5:0.5, and more preferably, further includes triethanolamine.

[0018] Li + With its small radius and strong polarization, lithium chloride can be used as an early strength agent to reduce drag and disperse particles. With appropriate dosage, it can change the fluidity and rheological properties of the slurry.

[0019] A composite early-strength agent is formed by using inorganic salt materials such as lithium chloride and sodium metasilicate. Combined with wet-mixed triethanolamine in water, it can effectively activate the cement base material and low-temperature active material, accelerate the reaction, shorten the initial setting time of low-temperature cement paste, and improve the early strength of cement stone.

[0020] Using inorganic salts such as lithium chloride and calcium sulfate in combination with triethanolamine can lower the crystallization point of cement slurry to below -5°C, thus providing antifreeze protection and alleviating the problem of hydration stagnation caused by freezing of water in cement slurry.

[0021] According to a specific embodiment of the present invention, preferably, the amount of triethanolamine added is 0.03-0.06 parts.

[0022] According to a specific embodiment of the present invention, preferably, the density of the glass microspheres is 0.35-0.45 g / cm³. 3 Its fracture strength is greater than 80 MPa.

[0023] According to a specific embodiment of the present invention, preferably, the dispersant comprises sodium polynaphthalene sulfonate.

[0024] According to a specific embodiment of the present invention, preferably, the water loss reducing agent comprises polyvinyl alcohol and / or 2-acrylamide-2-methylpropanesulfonic acid polymers.

[0025] According to a specific embodiment of the present invention, preferably, the retarder comprises hydroxyethylidene diphosphonic acid.

[0026] According to a specific embodiment of the present invention, preferably, the defoamer includes tributyl phosphate.

[0027] The present invention also provides a method for preparing the above-mentioned low-temperature cement slurry, which includes the following steps:

[0028] (1) Mix cement, cement base material, low-temperature active material, early strength agent, dispersant, water loss reducer and retarder in proportion to obtain dry mix;

[0029] (2) Mix the defoamer and water in proportion to obtain a wet mixture;

[0030] (3) The above dry mixture and wet mixture are mixed to obtain the low-temperature cement slurry.

[0031] According to a specific embodiment of the present invention, preferably, in step (1), the mixed raw materials further include a weight-reducing agent.

[0032] According to a specific embodiment of the present invention, preferably, when the early strength agent includes triethanolamine, the triethanolamine is mixed with the defoamer and water in step (2) to obtain a wet mixture; the other components of the early strength agent besides triethanolamine are added in step (1).

[0033] The present invention also provides the application of the above-mentioned low-temperature cement slurry in oil and gas well cementing.

[0034] According to a specific embodiment of the present invention, preferably, in the above application, the temperature at which the oil and gas well cementing is located is 0-5°C.

[0035] In summary, this invention provides a low-temperature cement slurry system by mixing oil well cement with low-temperature reinforcing materials, weight-reducing materials, dispersants, early-strength agents, and fluid loss reducing agents in a specific ratio. This system effectively solves the problems of cement stone shrinkage, cracking, slow strength development, and even water crystallization and freezing in cement slurry at 0°C in low-temperature environments (especially 0°C). It features early strength, micro-expansion, rust prevention, and adjustable comprehensive cement performance at low temperatures. Furthermore, it exhibits good rheological properties and no ash runoff issues, making it well-suited for cementing operations in deep water and polar regions. It shortens the cement slurry thickening time and meets the cementing quality requirements of oil and gas wells in extremely cold environments. The low-temperature cement slurry preparation method of this invention is simple, with low raw material and processing costs, enabling large-scale production and promotion. Detailed Implementation

[0036] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0037] Example 1

[0038] This embodiment provides a low-temperature cement slurry, the specific composition and preparation of which are as follows:

[0039] (1) The raw material composition by weight is shown in Table 1:

[0040] Table 1. Composition of raw materials for low-temperature cement slurry

[0041]

[0042] (2) Preparation of low-temperature cement slurry:

[0043] Weigh the materials according to the above proportions, and mix G-grade oil well cement, calcium sulfoaluminate, metakaolin, early strength agent (except triethanolamine), 2-acrylamide-2-methylpropanesulfonic acid polymer, sodium polynaphthalene sulfonate, and hydroxyethylidene diphosphonic acid evenly to obtain a dry mix.

[0044] Triethanolamine, tributyl phosphate, and water are mixed evenly to obtain a wet mixture;

[0045] At a rotation speed of 4000±200 r / min, the dry mixture is uniformly added to the wet mixture within 15 s. After the dry mixture is completely wetted, the mixture is stirred for another 35 s at a rotation speed of 12000±500 r / min to obtain the low-temperature cement slurry with a density of 1.90 g / cm³. 3 .

[0046] Example 2

[0047] This embodiment provides a low-temperature cement slurry, the specific composition and preparation of which are as follows:

[0048] (1) The raw material composition by weight is shown in Table 2:

[0049] Table 2 Composition of raw materials for low-temperature cement slurry

[0050]

[0051]

[0052] (2) Preparation of low-temperature cement slurry:

[0053] Weigh the materials according to the above proportions, and mix G-grade oil well cement, calcium sulfoaluminate, metakaolin, early strength agent (except triethanolamine), 2-acrylamide-2-methylpropanesulfonic acid polymer, glass microspheres, sodium polynaphthalene sulfonate, and hydroxyethylidene diphosphonic acid evenly to obtain a dry mix.

[0054] Triethanolamine, tributyl phosphate, and water are mixed evenly to obtain a wet mixture;

[0055] At a rotation speed of 4000±200 r / min, the dry mixture is uniformly added to the wet mixture within 50 s. After the dry mixture is completely wetted, the low-temperature cement slurry is obtained, which has a density of 1.80 g / cm³. 3 .

[0056] Example 3

[0057] This embodiment provides a low-temperature cement slurry, the specific composition and preparation of which are as follows:

[0058] (1) The raw material composition by weight is shown in Table 3:

[0059] Table 3. Composition of raw materials for low-temperature cement slurry

[0060]

[0061] (2) Preparation of low-temperature cement slurry:

[0062] Weigh the materials according to the above proportions, and mix G-grade oil well cement, calcium sulfoaluminate, metakaolin, early strength agent (except triethanolamine), 2-acrylamide-2-methylpropanesulfonic acid polymer, glass microspheres, sodium polynaphthalene sulfonate, and hydroxyethylidene diphosphonic acid evenly to obtain a dry mix.

[0063] Triethanolamine, tributyl phosphate, and water are mixed evenly to obtain a wet mixture;

[0064] At a rotation speed of 4000±200 r / min, the dry mixture is uniformly added to the wet mixture within 50 s. After the dry mixture is completely wetted, the low-temperature cement slurry is obtained, which has a density of 1.70 g / cm³. 3 .

[0065] Comparative Example 1

[0066] This comparative example provides a low-temperature cement slurry, the specific composition and preparation of which are as follows:

[0067] (1) The raw material composition by weight is shown in Table 4:

[0068] Table 4. Composition of raw materials for low-temperature cement slurry

[0069] Calcium sulfoaluminate 0 copies metakaolin 0 copies Early strength agent 0 copies Glass microspheres 0 copies Sodium polynaphthalene sulfonate 1.5 copies Hydroxyethylidene diphosphonic acid 2.5 portions Tributyl phosphate 0.2 copies water 44 copies

[0070] (2) Preparation of low-temperature cement slurry:

[0071] Weigh the materials according to the above proportions, and mix G-grade oil well cement, sodium polynaphthalene sulfonate, and hydroxyethylidene diphosphonic acid evenly to obtain a dry mixture.

[0072] Tributyl phosphate and water are mixed evenly to obtain a wet mixture;

[0073] At a rotation speed of 4000±200 r / min, the dry mixture is uniformly added to the wet mixture within 15 s. After the dry mixture is completely wetted, the mixture is stirred for another 35 s at a rotation speed of 12000±500 r / min to obtain the low-temperature cement slurry with a density of 1.90 g / cm³. 3 .

[0074] Comparative Example 2

[0075] This comparative example provides a low-temperature cement slurry, the specific composition and preparation of which are as follows:

[0076] (1) The raw material composition by weight is shown in Table 5:

[0077] Table 5 Composition of raw materials for low-temperature cement slurry

[0078]

[0079]

[0080] (2) Preparation of low-temperature cement slurry:

[0081] Weigh the materials according to the above proportions, and mix G-grade oil well cement, calcium chloride, sodium polynaphthalene sulfonate, and hydroxyethylidene diphosphonic acid evenly to obtain a dry mixture.

[0082] Tributyl phosphate and water are mixed evenly to obtain a wet mixture;

[0083] At a rotation speed of 4000±200 r / min, the dry mixture is uniformly added to the wet mixture within 15 s. After the dry mixture is completely wetted, the mixture is stirred for another 35 s at a rotation speed of 12000±500 r / min to obtain the low-temperature cement slurry with a density of 1.90 g / cm³. 3 .

[0084] Test Example 1

[0085] The comprehensive performance of the low-temperature cementing slurry system in the examples and comparative examples was evaluated according to the relevant provisions of the national standard GB / T19139-2012 "Test Methods for Cement in Oil Wells". The results are shown in Tables 6 and 7.

[0086] Table 6 Test Results

[0087]

[0088] As shown in Table 6, this low-temperature cement slurry exhibits good pumpability and rheological properties within the test temperature range of 0-10℃, with an API filtration loss of less than 60mL, excellent slurry stability, no free liquid, and a cement slurry density adaptability range of 1.70-1.90g / cm³. 3 This meets the performance requirements of cement slurry for cementing construction safety.

[0089] Table 7 Test Results

[0090]

[0091]

[0092] Table 7 compares the key performance parameters of Examples 1, Comparative Example 1, and Comparative Example 2 at the same density. At 10℃, the 24-hour compressive strength of the low-temperature cement slurry provided by this invention (Example 1) is significantly higher than that of the basic cement slurry (Comparative Example 1). Under the premise of similar compressive strength, the pumpability and fluidity of the low-temperature cement slurry provided by this invention are significantly better than those of the cement slurry with conventional reinforcing materials (Comparative Example 2). At 5℃, the 48-hour compressive strength of the low-temperature cement slurry provided by this invention (Example 1) is significantly higher than that of the basic cement slurry (Comparative Example 1). Under the premise of similar compressive strength, the pumpability and fluidity of the low-temperature cement slurry provided by this invention are significantly better than those of the cement slurry with conventional reinforcing materials (Comparative Example 2). At 0℃, the water in the basic cement slurry (Comparative Example 1) drops to its crystallization point, causing the cement stone to be in a "frozen" state. The hydration process stagnates, the strength development is slow, and the cement stone has almost no compressive strength. The cement stone with added conventional reinforcing materials (Comparative Example 2) shows depressions and shrinkage, and its compressive strength is lower than that of the low-temperature cement stone (Example 1) provided by this invention. It also flash-sets, and the cement slurry is in a solidified state. It can barely be stirred at 7000r. After being slowly stirred, the cement slurry becomes thinner, and a vortex can be stirred at 1600r.

[0093] Test Example 2

[0094] This test case examines the antifreeze effect of common antifreeze materials and their impact on compressive strength.

[0095] The mixture was cooled using a refrigerator, and the temperature of the ice-water mixture at the start of freezing was measured using a BOSCH thermometer. The cement slurry preparation process used in the following tests was as follows: 100 parts of G-grade oil well cement were used as the dry mix; antifreeze and water were mixed evenly in different proportions to obtain a wet mix (the percentage of antifreeze added below is the volume fraction of antifreeze in water); the dry mix was evenly added to 44 parts of the wet mix within 50 seconds at a speed of 4000±200 r / min. After the dry mix was completely wetted, the cement slurry used for Test Example 2 was obtained. The amount of each component added was calculated based on the mass of the obtained cement slurry as 100%. The results are shown in Tables 8-10.

[0096] Table 8

[0097]

[0098] Table 9

[0099]

[0100]

[0101] Table 10

[0102] 4% calcium chloride solution Ice-water mixture (lots of ice) freeze 4% lithium chloride solution ice water mixture freeze 10% sodium chloride water freeze 10% lithium chloride water Water (partially iced)

[0103] As shown in Tables 8-10, liquid sodium silicate has no antifreeze effect when added at a concentration of 20-40%; 40% ethylene glycol can provide antifreeze protection at -18℃; and 45%-50% commercial glass cleaner (wood alcohol) can provide antifreeze protection at -18℃.

[0104] The effect of antifreeze on the compressive strength of cement was further investigated, and the results are shown in Table 11.

[0105] Table 11

[0106] Blank control group (water only) 6.9+6.7 1.892 25% ethylene glycol 3.1+4.1 1.94 30% ethylene glycol 1.8+2.2 1.92 30% commercial wood alcohol The intensity did not rise 1.90 4% calcium chloride solution 11.1+14.2 1.90 (Lower Gray Flash Condensation) 4% lithium chloride solution 11.3+13.5 1.90

[0107] As shown in Table 11, the commonly used antifreeze agents mentioned above all have a negative effect on the development of compressive strength, and calcium chloride will cause the problem of flashover in the lower ash.

[0108] Test Example 3

[0109] The thickening time of the low-temperature cementing slurry system in the example was evaluated according to the relevant provisions of the national standard GB / T19139-2012 "Test Methods for Cement in Oil Wells". The results are shown in Table 12.

[0110] Table 12

[0111]

[0112]

[0113] As shown in Table 12, the low-temperature cement slurry system provided by the present invention has an adjustable thickening time of 100-300 min at a temperature of 0-10℃.

[0114] In summary, the low-temperature reinforcing cement slurry material and the configured cement slurry system of this invention exhibit excellent comprehensive performance. The resulting low-temperature cement slurry system has an adjustable thickening time of 100-300 minutes, does not freeze or crack at 0°C, and has a compressive strength greater than 10 MPa / 48h at 0°C. It is suitable for cementing operations in low-temperature environments and effectively solves problems such as cement shrinkage, cracking, slow strength development, water crystallization in cement slurry at 0°C, and freezing. It shortens the cement slurry setting time and improves the early strength of cement stone, showing promising application prospects in cementing operations in deep water, polar regions, and other extremely cold formations.

[0115] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0116] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0117] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A low-temperature cement slurry, comprising, by weight, the following components: 100 parts Grade G oil well cement, 10 parts calcium sulfoaluminate, 10 parts metakaolin, 4 parts early strength agent, 2.5 parts 2-acrylamide-2-methylpropanesulfonic acid polymer, 1.5 parts sodium polynaphthalene sulfonate, 2.5 parts hydroxyethylidene diphosphonic acid, 0.2 parts tributyl phosphate and 50 parts water; The early strength agent is lithium chloride, sodium sulfate, sodium aluminate and triethanolamine in a weight ratio of 2.5:1.2:0.5:0.

05.

2. The low-temperature cement slurry according to claim 1, wherein, The metakaolin has a purity of ≥95% and a density of ≥2.50 g / cm³. 3 , mesh number ≥ 5000 mesh.

3. The method for preparing low-temperature cement slurry according to claim 1 or 2, comprising the following steps: (1) G-grade oil well cement, calcium sulfoaluminate, metakaolin, lithium chloride, sodium sulfate, sodium aluminate, 2-acrylamide-2-methylpropanesulfonic acid polymer, sodium polynaphthalene sulfonate, and hydroxyethylidene diphosphonic acid are mixed in proportion to obtain a dry mixture; (2) Triethanolamine, tributyl phosphate and water are mixed to obtain a wet mixture; (3) The above dry mixture and wet mixture are mixed to obtain the low-temperature cement slurry.

4. The application of the low-temperature cement slurry as described in claim 1 or 2 in cementing oil and gas wells.

5. The application according to claim 4, wherein, The temperature at which the oil and gas well cementing is performed is 0-5℃.

Citation Information

Patent Citations

  • Low temperature rapid hardening grouting material for offshore oil well and preparation method thereof

    CN105199692A

  • Low-temperature high-strength tough cement paste and preparation method and application thereof

    CN106986584A

  • Preparation method of composite early strength agent and application of composite early strength agent in deepwater well cementation

    CN113683336A